Day-of-the-Week Effect in Returns in the Indian Capital Market : Evidence from the National Stock Exchange - Khanna, Vandana (Indian Journal of Research in Capital Markets, 2015)
Evidence of empirical regularities in security returns leads to a rejection of the joint hypothesis that the asset pricing model used is adequate and that the markets are efficient. This paper examined the stability of the Day-of-the-Week effect in returns and volatility in the Indian capital market coveringÂ the period from November 3, 1994 to March 31, 2006 by considering the impact of capital market reforms, especially the Rolling Settlement Effect on the trading days of the week on the Indian stock exchange. The study is based on 203 companies listed on the National Stock Exchange. The results revealed the absence of Day-of-the-Week effect for the Aggregate period ; whereas, the Monday effect was found for the Post-Liberalization period. However, during the Pre-Rolling Settlement period, the Friday effect was documented ; whereas, a slight Wednesday effect was found for the Post-Rolling Settlement period. The anomaly Day-of-the-Week effect suggested that market participants could predict the market and can benefit from the market by timing their plans for investment and sale of securities.